(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The article discusses the factors, problems and difficulties affecting the study of Russian in Uzbek groups, and comments on the existing textbooks. Suggestions were made for the development of students’ Russian language skills in military academies.